Iraq : final assessments of the Special Inspector General and post-U.S. withdrawal developments - Ryder, Gustavo D.; Katzman, Kenneth (Politics and economics of the Middle East., 2013)
Regarding U.S. relief and reconstruction plans, programs, and operations in Iraq, the Special Inspector General for Iraq Reconstruction (SIGIR) provides independent and objective: oversight and review through comprehensive audits, inspections, and investigations; advice and recommendations on policies to promote economy, efficiency, and effectiveness; prevention, detection, and deterrence of fraud, waste, and abuse; and information and analysis to the Congress, the Secretary of State, the Secretary of Defense, and the American people. This book provides a review of SIGIR's history, delving int.